Implementasi Kebijakan Pembangunan Monumen Reog di Kabupaten Ponorogo - afif, aria; manggalou, singgih (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine how the implementation of the reog monument development policy in Ponorogo Regency is analyzed using indicators of the policy implementation model from the Edwards III Model (Tachjan, 2016). The type of research used is qualitative research with data collection techniques in the form of observation, interviews, and documentation. The results showed that all indicators of the policy implementation model for the development of the reog monument in Ponorogo Regency had been achieved, which caused researchers to conclude that the implementation of the Reog Monument development policy in Ponorogo Regency had gone well. Effective coordination between the Tourism Office and related parties, including the DPRD, ensured budget arrangements and clear information dissemination. Overall. The policy was well implemented thanks to competent human resources, with a budget of 50 billion rupiah realized as planned. With approval from the Regent of Ponorogo and the Chairman of the DPRD. The bureaucratic structure shows an effective division of tasks, as well as daily reporting and efficient communication. So it can be concluded that the implementation of the reog monument development policy in Ponorogo Regency has been well implemented.